SOCIAL HOUSING IN PARIS WITH HISTORICAL ASPECT APPROACHING - Dian Widareni; Agung Dwiyanto; Atik Suprapti (IMAJI, 2012)
This booklet aims to give an overview of the social housing sector in Europe. The intention is to identify general patterns and important trajectories, that are likely to impact on future policy. The goal is not to provide detailed descriptions of the sector in every country, but to understand its key attributes and to clarify major trends.There are definitional issues about social housing such as around the position of co-operatives, time limited subsidies, and the role of private suppliers. The profile of the social housing stock differs across countries in terms of age, housing type, and the percentage located on estates. Social housing serves different client groups, some of it for the very poor, while in others it is for working families or even the middle classes while the very poor are accommodated. Actually, the social housing sector generally for number of single-parent families, the elderly, and the poor.Social housing efforts are also being made to introduce a greater mix in the existing stock and to use public assets more effectively.The first thing that begins the study is trying to find out the definition of social housing and some other based things about it, such as the standard of the layout itself. Trying to obey the regulation on the site around the neighbourhood is also be considered.The concept of the design is based on the surrounding condition. Trying to maximize the potential of the site is the main purpose that need to be reached. The form of the building is refered to the tourism point and the meeting point around the site.